ANALISIS IMPLEMENTASI SISTEM TRANSAKSI NON TUNAI DALAM PENGELOLAAN KEUANGAN DAERAH (Studi Pada Pemerintah Daerah Kabupaten Kampar) - Elmizar Elmizar; Kasmadi Kasmadi (STIE Bangkinang Publishing, 2020)
The application of a non-cash transaction system is a system of development in the transparency of regional financial management. As a follow-up to the implementation of non-cash transactions, the Government of Kampar Regency has implemented a non-cash transaction in full on January 1, 2018 in accordance with the Kampar Regent's Regulation Number: 61 Year 2017 dated December 15, 2017 concerning the Non-Cash Payment System within the Kampar Regency Government. The purpose of this study is to find out the process of implementing a non-cash transaction system in local financial management in Kampar Regency, then to find out the problems and constraints as well as steps for improvement in the process of implementing a non-cash transaction system in regional financial management. The research method used in this research is descriptive qualitative research.The implementation of non-cash transactions by the Kampar District Government has shown a 75% percentage of the level of